The change in weight perception of weight status among the overweight: comparison of NHANES III (1988-1994) and 1999-2004 NHANES - Starke-Reed Pamela; Hubbard Van S; Fisher Rachel A; Johnson-Taylor Wendy L; Eggers Paul S (BMC, 2008)
Abstract Objectives This study seeks to determine whether perception of weight status among the overweight has changed with the increasing overweight/obesity prevalence. Methods The perception of weight status was compared between overweight participants (BMI between 25.0-29.9 kg/m2) from NHANES III (1988-1994) and overweight participants from NHANES 1999-2004. Perception of weight status was assessed by asking participants to classify their weight as about the right weight, underweight or overweight. Comparisons were made across age groups, genders, race/ethnicities and various income levels. Results Fewer overweight people during the NHANES 1999-2004 survey perceived themselves as overweight when compared to overweight people during the NHANES III survey. The change in distortion between the survey periods was greatest among persons with lower income, males and African-Americans. Conclusion The increase in overweight/obesity between the survey years (NHANES III and NHANES 1999-2004 has been accompanied with fewer overweight people perceiving themselves as overweight.